2013
DOI: 10.1039/c3ra23378b
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous formation of branched nanochains from room temperature molten amides: visible and near-IR active, SERS substrates for non-fluorescent and fluorescent analytes

Abstract: Highly stable, branched gold nanoworms are formed spontaneously in an acetamide-based room temperature molten solvent without any additional external stabilizing or aggregating agent. The nanoworms can be anchored onto solid substrates such as indium tin oxide (ITO) without any change in morphology. The anchored nanoworms are explored as substrates for surface enhanced Raman scattering (SERS) studies using non-fluorescent 4-mercaptobenzoic acid (4-MBA) and fluorescent rhodamine 6G (R6G) as probe molecules. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 80 publications
(103 reference statements)
3
12
0
Order By: Relevance
“…The observed bands are similar to those found in previous works [10,14,16,33]. 4-MBA shows two strong SERS bands at 1587 (ring C-C stretch, asymmetric C-H in-plane bending) and 1080 cm −1 (aromatic ring breathing, symmetric C-H in-plane bending, C-S stretching) [32,33]. The band observed around 1417 cm −1 was assigned to v s (COO − ), symmetric stretching vibration of the carboxylate group.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…The observed bands are similar to those found in previous works [10,14,16,33]. 4-MBA shows two strong SERS bands at 1587 (ring C-C stretch, asymmetric C-H in-plane bending) and 1080 cm −1 (aromatic ring breathing, symmetric C-H in-plane bending, C-S stretching) [32,33]. The band observed around 1417 cm −1 was assigned to v s (COO − ), symmetric stretching vibration of the carboxylate group.…”
Section: Methodssupporting
confidence: 90%
“…The band observed around 1417 cm −1 was assigned to v s (COO − ), symmetric stretching vibration of the carboxylate group. At pH 2, the broad feature rises at 1296 and 1318 cm −1 belongs to the ring inplane C-H bending mode and C-O stretching mode, respectively [32]. It indicates that the carboxylate group is protonated.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to previous studies, the predominant bands were located at 1084, 1188, and 1590 cm À1 , which were assigned to a 1 modes of vCS, dCH, and vCC. 21,22 In the SERS spectrum, the vCS band at 1084 cm À1 shied to 1079 cm À1 , due to Ag-S bond formation. The band dCH at 1188 cm À1 shied to 1180 cm À1 , and the vCC shied from 1590 cm À1 to 1587 cm À1 aer pMBA adsorption on the silver surface.…”
Section: Sers Property Of the As-prepared Go/agnp Hybridsmentioning
confidence: 99%
“…It was also demonstrated both theoretically and experimentally that strong electromagnetic field enhancements would arise at the interparticle junctions in nanoparticle aggregates upon interaction with visible radiation. 31,32 Concentration dependent studies were carried out by dipping the Ir modified glass substrate into 2 mL of different concentrations of the analyte (1 mM to 0.1 mM) for 30 minutes and subsequently drying the substrate before Raman spectral measurements were carried out. The detection limit for 4-MPy in the present study is observed to be 0.1 mM.…”
mentioning
confidence: 99%